The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00431-017-3076-8
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Crohn disease is characterized by Th1 in the terminal ileum and Th1/Th17 immune response in the colon

Abstract: New onset pediatric CD is characterized by Th1 response in ileum and mixed Th1/Th17 response in the colon, with elevated expressions of innate IL-6 and IL-1β. SOCS1/SOCS3 expressions seem to be insufficient for the regulation of the immune response. The reduction in MDR1 expression points to its role in the disease pathogenesis. What is Known: • CD is characterized by an aberrant immune response What is New: • The immune response in new onset pediatric CD differs between terminal ileum and colon • MDR1 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Previously, we have shown that N-CMFs suppress IFN-γ production by activated T cells in a PD-L1-dependent manner ( 32 ). An increase in the IFN-γ-producing Th1 cells in CD LP and a decrease in UC LP have been recently observed by several investigators ( 43 45 ). We also observed an increase in IFN-γ levels in the inflamed mucosa of patients with CD colitis (Figure 5 ).…”
Section: Resultsmentioning
confidence: 62%
“…Previously, we have shown that N-CMFs suppress IFN-γ production by activated T cells in a PD-L1-dependent manner ( 32 ). An increase in the IFN-γ-producing Th1 cells in CD LP and a decrease in UC LP have been recently observed by several investigators ( 43 45 ). We also observed an increase in IFN-γ levels in the inflamed mucosa of patients with CD colitis (Figure 5 ).…”
Section: Resultsmentioning
confidence: 62%
“…Indeed, Th2 related cytokines such as IL-4, IL-5, IL-6, and IL-13 are increased in UC patients [197,198]. On the contrary, Th1-related cytokines such as TNF, IFN-γ, and IL-12 are increased in the colonic mucosa of CD [199,200].…”
Section: Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…In addition, it has been demonstrated that IL-5, IL-13, IL-15 and IL-33 mRNA levels in DC patients were significantly increased when compared to both DC and control [5]. Interestingly, it was shown that pediatric CD is characterized by Th1 in the terminal ileum and Th1/Th17 immune response in the colon [54]. However, currently it is considered that Th1 and Th2 immune responses do not represent the complexity of immune responses measured by intestinal T cells.…”
Section: Revisiting Th1 and Th2 Lymphocytesmentioning
confidence: 99%